2016
DOI: 10.1371/journal.pone.0147182
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Cognition, Gender and Monocyte Activation among HIV Infected Individuals in Nigeria

Abstract: The potential role of gender in the occurrence of HIV-related neurocognitive impairment (NCI) and associations with markers of HIV-related immune activity has not been previously examined. In this study 149 antiretroviral-naïve seropositive subjects in Nigeria (SP, 92 women and 57 men) and 58 seronegative (SN, 38 women and 20 men) were administered neuropsychological testing that assessed 7 ability domains. From the neuropsychological test scores was calculated a global deficit score (GDS), a measure of overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 49 publications
3
61
0
Order By: Relevance
“…Details of these are described in our other reports (Akolo et al 2014; Royal et al 2016; Jumare et al 2017). Participants were screened for effort using the Hiscock Digit Memory Test, and for depression with the Beck Depression Inventory (Beck et al 1996).…”
Section: Methodsmentioning
confidence: 95%
“…Details of these are described in our other reports (Akolo et al 2014; Royal et al 2016; Jumare et al 2017). Participants were screened for effort using the Hiscock Digit Memory Test, and for depression with the Beck Depression Inventory (Beck et al 1996).…”
Section: Methodsmentioning
confidence: 95%
“…Sex differences in the HIV-1 Tg rat expand on differences observed in HIV-1 seropositive individuals. Recent studies have reported significantly greater neurological impairment in HIV-1 seropositive women, in comparison to HIV-1 seropositive men4344. The effect of sex on the progression of neurocognitive impairments in HIV-1 seropositive individuals has been relatively understudied; the need for longitudinal study is critical45.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from the Women’s Interagency HIV Study (WIHS), the largest study ( N = 1521) of HIV disease progression in women to date (Maki et al, 2014) demonstrated that HIV+ women performed significantly more poorly than HIV–women on measures of verbal episodic memory, but not on measures of processing speed (Symbol Digit Modalities Test) or executive functioning (Stroop, Trail Making Test B), which are typically impaired among HIV+ men (Woods et al, 2009). Maki et al (2014) speculated that verbal memory deficits might be more prominent among HIV+ women than among men, but limited evidence is available to address this question, since few studies have compared neurocognitive performance of HIV+ men and women directly (Behrman-Lay et al, 2016; Hestad et al, 2012; Robertson et al, 2005; Royal et al, 2004) with inconsistent results.…”
mentioning
confidence: 99%